Increasing Basketball Passing Learning Results Through Modifications of Traditional Games of Fort And Drive Cart in High School Students - Marhenes, Raden Klid; Sumarni, Sri; Hartati, Hartati; Yusfi, Herri; Iyakrus, Iyakrus (Department of Physical Education, Sport, Health and Recreation, 2021)
The purpose of this study was to determine the improvement of basketball passing learning outcomes through modification of the traditional fort and pushcart games for junior high school students. The method used in this research is Classroom Action Research with Kemmis and Mc.Taggart models through 2 cycles with stages: planning, implementation, observation and reflection. The subjects in this study were students of class VIII.2 SMPN 1 Talang Kelapa and the research sample amounted to 32 people. The results showed that there was an increase in basketball passing learning outcomes through modifications to the traditional fort and pushcart games for junior high school students. The results of the pre-cycle of students who were able to achieve a completeness score were 13 people with a graduation percentage of 41%. After learning cycle 1 the number of students who achieved completeness scores was 23 people with a passing percentage of 71%. Meanwhile, after cycle 2, there were 29 students who achieved the completeness score with a percentage of 91%, which means that the target of classical learning success, namely 85% of students who passed, had been achieved. It can be concluded that the modification of the traditional game fortification and pushcart can be used as a learning model to improve basketball passing for junior high school students.